Supporting health and wellbeing in health care employees: a documentary review of organizational policies, strategies and frameworks - Hoyle, Louise Patricia; Ryde, Gemma Cathrine; Coulter, Jamie; Rollason, Jennie (Frontiers in Sports and Active Living, 2024)
Background: Health care workers are crucial for a productive and thriving health care system, yet the health and lifestyle behaviour of key groups within this workforce (for example nurses and healthcare assistants/support workers) is typically poor. The extent of health and wellbeing documents that guide action towards improving their health and wellbeing is unknown. Using one health care system, NHS Scotland, as an example, the aim of this study was to assess the number of NHS health boards with workplace documents focused on health and wellbeing of employees, the quality of these documents and the extent to which they reference lifestyle behaviours, namely physical activity.Methods: Documentary analysis was undertaken on employee health and wellbeing policies (and wider documents). These were sourced through online searches on Google search engine and Freedom of Information Requests sent to all 14 Scottish NHS Health Boards. Titles and content were assessed for relevance to employee health and wellbeing. Content analysis was used to analyse the included documents against eight predefined codes.Results: Thirteen documents were retrieved with 11 of the 14 Health Boards having at least one relevant document. The content varied greatly between documents with regards to how many reported the eight codes and the quality of content within these. Nine documents mentioned physical 2 activity but mainly in relation to current activities rather than in the context of a future healthy workforce.Conclusions: Despite the importance of a healthy, health care workforce, more work is needed to ensure high level documents are able to support these efforts, especially with reference to lifestyle behaviours.